2018
DOI: 10.1111/dme.13612
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and external validation of a prediction model for adverse outcomes among inpatients with diabetes

Abstract: The prediction model to identify patients with diabetes at high risk of developing an adverse event while in hospital performed well in temporal and external validation. The externally validated prediction model is a novel tool that can be used to improve care pathways for inpatients with diabetes. Further research to assess clinical utility is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…However, the RPM-DKD established by logistic regression did not perform well. Furthermore, prediction models can become obsolete with change in population demography, better therapeutic options and care pathways, and improvement in data recording 34. In the future, it may be possible to build a DKD prediction model by deep learning methods in order to improve the prediction of DKD occurrence and progression; many studies have applied deep learning with proven success 35–39…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the RPM-DKD established by logistic regression did not perform well. Furthermore, prediction models can become obsolete with change in population demography, better therapeutic options and care pathways, and improvement in data recording 34. In the future, it may be possible to build a DKD prediction model by deep learning methods in order to improve the prediction of DKD occurrence and progression; many studies have applied deep learning with proven success 35–39…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, prediction models can become obsolete with change in population demography, better therapeutic options and care pathways, and improvement in data recording. 34 In the future, it may be possible to build a DKD prediction model by deep learning methods in order to improve the prediction of DKD occurrence and progression; many studies have applied deep learning with proven success. [35][36][37][38][39] CONCLUSION Our independent external validation study revealed that, in patients with T2DM, the RPM-DKD cannot accurately predict the risk of DKD occurrence and progression.…”
Section: Future Researchmentioning
confidence: 99%